2015
DOI: 10.1074/jbc.a111.279893
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of heme oxygenase-1 to mitochondria is a novel cytoprotective mechanism against non-steroidal anti-inflammatory drug-induced mitochondrial oxidative stress, apoptosis, and gastric mucosal injury.

Abstract: PAGES 39392 and 39397:The same images of gastric mucosal sections were used to represent the results of different experiments in Fig. 1A and Fig. 7 by mistake. The correct gastric mucosal sections after indomethacin treatment for 12 and 24 h are now shown in Fig. 1A, and the correct gastric mucosal sections at 0, 4, and 48 h after indomethacin treatment, 48 h after indomethacin and zinc protoporphyrin treatment, and 4 h after zinc protoporphyrin treatment are now shown in Fig. 7. These corrections do not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…We found a significant portion of HO-1 colocalized in the mitochondrial compartment indicating an interesting link between HO-1 overexpression and mitochondrial dysfunction. Some previous studies have shown HO-1 translocation to mitochondria under different stress conditions, and most of these studies postulated a compensatory protective effect of HO-1 by scavenging extra heme load (65,66). It is also possible that HO-1 translocation to mitochondria can lead to localized generation of toxic levels of CO upon degradation of the heme (62).…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant portion of HO-1 colocalized in the mitochondrial compartment indicating an interesting link between HO-1 overexpression and mitochondrial dysfunction. Some previous studies have shown HO-1 translocation to mitochondria under different stress conditions, and most of these studies postulated a compensatory protective effect of HO-1 by scavenging extra heme load (65,66). It is also possible that HO-1 translocation to mitochondria can lead to localized generation of toxic levels of CO upon degradation of the heme (62).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that expression of HO-1 targeted to mitochondria attenuated oxidative stress (43). These observations, taken together, suggest that mitochondrial translocation of HO-1 could serve as a cytoprotective mechanism against possible mitochondrial dysfunction induced by oxidative or metabolic insults (32). However, hemin or LPS-induced mitochondrial accumulation of HO-1 was associated with decreased mitochondrial heme content and reduced expression of heme-sensitive subunit I of complex IV with loss of activity (33).…”
Section: Effect Of Oxidized Hb Exposure On E10 Cellsmentioning
confidence: 97%
“…Regardless of differences in the rates of heme release from these proteins, confocal microscopy images and immunoblotting of purified mitochondrial fractions confirmed that a portion of expressed HO-1 translocated into the mitochondria. HOs are predominantly localized in the microsomes, but translocation into the mitochondria under certain stressful conditions has been reported (32,34). Mitochondrial translocation of HO-1 might enable detoxification of accumulated heme as a result of oxidation and unfolding of Hb.…”
Section: Effect Of Oxidized Hb Exposure On E10 Cellsmentioning
confidence: 99%
“…In addition, Park et al (2011) showed that certain isoflavones can induce HO-1 in primary astrocytes and this can be accompanied by its translocation from the ER to mitochondria (Bindu et al, 2011;Bansal et al, 2013). The first intermediate step of HO-1 catalysis produces Fe 21 , an effective component of the Fenton reaction.…”
Section: Redox Active Isoflavone In Lung Cancermentioning
confidence: 99%